Gambling for Profit : Historical Contingency and Jagged Growth - Chambers, Kerry, 1958- (Book collections on Project MUSE., 2011)
Gambling for Profit is unique among studies of gambling's twentieth-century growth thanks to Kerry G.E. Chambers's strong analytical framework - investigating not only the political aspects of legalization, but also the sociocultural factors that influence popular adoption. Chambers provides a useful chronological examination of the electronic gambling phenomenon, as well as comparative data on dates of introduction and revenues across twenty-three countries. Gambling for Profit provides a dynamic model to explore the legalization of gambling and stresses the inadequacy of seeking universal explanations for gambling's entrenchment within particular cultures."--Pub. desc.